The senescent bystander effect is caused by ROS-activated NF-κB signalling. (March 2018) - Nelson, Glyn; Kucheryavenko, Olena; Wordsworth, James; von Zglinicki, Thomas
Graphical abstract: Highlights: Mitochondrial dysfunction in cell senescence is sufficient for NF-κB activation via ROS. NF-κB activation drives the senescent bystander effect. IL-6 and IL-8 secretion in senescence is only partly dependent on NF-κB. IL-6 and IL-8 are not essential mediators of the bystander effect. Abstract: Cell senescence is an important driver of the ageing process. The accumulation of senescent cells in tissues is accelerated by stress signals from senescent cells that induce DNA damage and ultimately senescence in bystander cells. We examine here the interplay of senescence-associated mitochondrial dysfunction (SAMD)—driven production of reactive oxygen species (ROS) and senescence-associated secretory phenotype (SASP) in causing the bystander effect. We show that in various modes of fibroblast senescence ROS are necessary and sufficient to activate the transcription factor nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), which facilitates a large part of the SASP. This ROS-NF-κB axis causes the DNA damage response in bystander cells. Cytokines IL-6 and IL-8 are major components of the pro-inflammatory SASP in senescent fibroblasts. However, their activation in senescence is only partially controlled by NF-κB, and they are thus not strong candidates as intercellular mediators of the bystander effect as mediated by the ROS-NF-κB axis.